The mediating role of parent-child bonding for the prospective association of prenatal depressive symptoms with child development at 14 months postpartum - Ariane Göbel; Caroline Hilpert; Victoria Weise; Judith T. Mack; Susan Garthus-Niegel (BMC Pediatrics)
Abstract Background Depressive symptoms in the perinatal period as well as difficulties developing an emotional bond towards the child have been described as potential risk factors for poor child development. Few studies have investigated the mediating role of parent-child bonding for the association between prenatal depressive symptoms and child outcomes. Research on this association is especially scarce regarding the paternal perspective. This study investigated the prospective association between both parents’ prenatal depressive symptoms and child development, taking the mediating role of parent-child bonding into account. Methods Data of 1,178 mothers and 743 fathers were drawn from the prospective longitudinal cohort study “Dresden Study on Parenting, Work, and Mental Health” (DREAM). To investigate the prospective association between depressive symptoms during pregnancy and eight weeks postpartum (self-report, Edinburgh Postnatal Depression Scale), parent-child bonding at eight weeks postpartum (self-report, Postpartum Bonding Questionnaire), and child development at 14 months postpartum (parent-report, Ages and Stages Questionnaire-3), multiple regression and mediation analyses were conducted individually for both parents, including the confounders parental age, education, child’s sex assigned at birth, prematurity, and perceived social support. Results In both parents, a statistically significant small-sized mediating effect of parent-child bonding for the association between prenatal depressive symptoms and child development was found, with higher depressive symptoms being associated with more parent-child bonding impairment, which was associated with poorer child development. Paternal depressive symptoms were not directly associated with child development, whereas higher levels of maternal prenatal depressive symptoms were directly associated with better child development at 14 months postpartum. After additionally controlling for postpartum depressive symptoms, the association between prenatal depressive symptoms and parent-child bonding was no longer significant, and a positive association between paternal prenatal depressive symptoms and child development emerged. Conclusions Our results underline the importance of addressing depressive symptoms in the context of perinatal care to support parents experiencing mental health problems or struggles with the adjustment to parenthood early on. Future research on the complex dynamics of mental health, parent-child bonding, and child development is needed to replicate our findings. Our study highlights the relevance of including the perspective of both parents into research and clinical practice.